Bioremediation Experience Collected in “Bioengineering in Remediation of Polluted Environments”: A Closing Perspective by Guest Editors - Marco Zeppilli; Bruna Matturro (Bioengineering, 2025)
The article collection entitled “Bioengineering in Remediation of Polluted Environments” was launched in September 2021 [...]